Crystal structure and Hirshfeld surface analysis of 2-amino-4-methoxy-6-methylpyrimidinium 2-hydroxybenzoate - Jeevaraj, Muthaiah; Sivajeyanthi, Palaniyappan; Edison, Bellarmin; Thanigaimani, Kaliyaperumal; Balasubramani, Kasthuri; Razak, Ibrahim Abdul (International Union of Crystallography, 2017)
In the title molecular salt, C6H10N3O+·C7H5O3 −, the cation is protonated at the N atom lying between the amine and methyl substituents and the dihedral angle between the carboxyl group and its attached ring in the anion is 4.0 (2)°. The anion features an intramolecular O—H⋯O hydrogen bond, which closes an S(6) ring. The cation and anion are linked by two N—H⋯O hydrogen bonds [R 2 2(8) motif] to generate an ion pair in which the dihedral angle between the aromatic rings is 8.34 (9)°. Crystal symmetry relates two ion pairs bridged by further N—H⋯O hydrogen bonds into a tetrameric DDAA array. The tetramers are linked by pairs of C—H⋯O hydrogen bonds to generate [100] chains. Hirshfeld surface and fingerprint plot analyses are presented.